Toward a Victim-Oriented Digital Justice Model: Legal Protection for Personal Data Misuse Under the Personal Data Protection Law - Nur Khalimatus Sa’diyah; Raden Besse Kartoningrat; Umi Enggarsasi (Jurnal Hukum, 2026)
This study examines legal protection for victims of personal data misuse in Indonesia within the context of Society 5.0 by addressing three objectives: analyzing existing legal protections under the Personal Data Protection (PDP) Law, identifying gaps between normative regulation and law enforcement practice, and formulating a victim-oriented digital justice model. Using a normative and conceptual approach, this study analyzes Law Number 27 of 2022 and related regulations through qualitative descriptive methods. The findings reveal significant structural weaknesses in Indonesia’s personal data protection regime. Normatively, the PDP Law has not explicitly positioned victims as rights-bearing subjects entitled to restitution, compensation, and digital rehabilitation. Practically, enforcement remains compliance-oriented, relying heavily on administrative sanctions while neglecting victims’ access to justice, redress, and recovery. Institutional fragmentation, limited evidentiary access, and the absence of an independent data protection authority further weaken victim protection. This study proposes a victim-oriented digital justice model that integrates rights-based enforcement, restorative justice principles, and international human rights standards, particularly the UN Basic Principles on Remedy and Reparation. The model emphasizes legal recognition of victims, effective access to justice, and comprehensive redress mechanisms to ensure meaningful protection and restoration of victims’ rights in the digital era.